Kontribusi Al-Kindi pada Pembentukan Etika Islam dalam Analisis Filsafat Hidup - Mujiburrohman, Mujiburrohman; Priyanto, Priyanto; Jumingan, Jumingan; Akbar, Muhammad Aidil (TSAQOFAH, 2026)
Islamic philosophy functions not only as an intellectual apparatus but also as a practical guide in everyday life, in which Al-Kindi’s contribution occupies an important position as a bridge between the tradition of Greek philosophy and the Islamic thought that developed in the Arab world. This article aims to identify Al-Kindi’s philosophy of life and analyze its relevance in the context of contemporary plural societies by examining how his ideas can be applied to build morality and ethics in diverse communities. The study employs a qualitative approach using a literature review method, drawing on relevant journal articles and books concerning Al-Kindi’s thought on Islamic ethics. The findings indicate that Al-Kindi’s contribution to Islamic ethics is highly significant and provides a strong foundation for the subsequent development of Islamic philosophical thought, particularly through his exposition of the relationship between God, human beings, and the universe as a comprehensive ethical basis. The significance of his views lies in their capacity to integrate Islamic teachings with classical Greek philosophy and in his emphasis on the role of education in shaping individual character and morality. This study concludes that Al-Kindi’s ethical thought is highly relevant in the modern era, particularly as a conceptual framework for strengthening public ethics and serving as a bridge for interreligious and intercultural dialogue within plural societies.